1.Выполните действия: а) (6х3- 2х5+х) + (-8х3+3х5- 4х2);
б) -(-х2у2+ 4х – 3х2у-8)+(2-3ху2-х2у2+у);
в) 5х(х+4)- х(6-2х2)- 2/3(6х2- 12х3).
2. Найдите значение выражения:
а) (12а2+ 5аb) – 7а2- (5а2+ 3аb), если а=-0,25, b=1,4;
б) -4х(х2-х-3) +2х(2х2+х-5), если х=-3;
в) (5а(а-4b) + 12ab)∙2b+16ab2, если а=3, b=1,2.
3. Решите уравнения:
а) (5х2+х3-7) – (2х3-5+4х2)= - (1+х3);
б) х(7х-1) – 3(х2-2х+4) = 2х(3+2х);
в) (2х+2)/5 - х/2 = (х+3)/4 .
4. Доказать, что выражение не зависит от значений переменных:
(х3+3х2-3х) + (х6+4х3-7х) – (5х3-10х-5).
4х²-2х+3=0
D=(-2)²-4×4×3=4-48=-44 D<0, уравнение не имеет корней
----------------------------------------------------------------------------
5х²+26х=24
5х²+26х-24=0
D=26²-4×5×(-24)=676+480=1156 D>0
х₁=
х₂=
х₁=0,8
х₂=-6
-------------------------------------------------------------------------
3х²-5х=0
D=5²-4×3×0=25-0=25 D>0
х₁=
х₂=
х₁=1,667
х₂=0
--------------------------------------------------------------------
6-2х²=0
-2х²+6=0
D=0²-4×(-2)×6=0+48=48 D>0
х₁=
х₂=
х₁=-1,732
х₂=1,732
------------------------------------------------------------------
t²=35-2t
t²+2t-35=0
D=2²-4×1×(-35)=4+140=144
t₁=
t₂=
t₁=5
t₂=-7